Local Chickens Farming System Characteristics and Their Genetic Resources Management in Seno Province of Burkina Faso - Ouédraogo, R. W.; Tindano, K.; Traoré, F. G.; Tapsoba, S. A. R.; Sanou, M.; Tamboura, H. H.; Bayala, B.; Traoré, A. (Faculty of Animal Science, Bogor Agricultural University, 2023)
Local genetic resources have an important place in poultry production in Africa. However, knowledge of these genetic resources and their breeding systems is quite often limited. This study was carried out in Seno province/Burkina Faso and aimed to characterize the local chicken production system, the genetic resources used and their management in this area. A survey was conducted including 185 chicken farmers in a rural area. The snowball sampling method was used to co-opt interviewees and, face-to-face interviews were done. The questionnaire includes closed and open-ended questions. Production system characteristics showed that local chickens were bred in free-range production system with few inputs. There were multiple production purposes such as self-consumption (meat and eggs), saving, sale, making donation to strangers. The sale of chickens was ranked as the main purpose with 0.48 as the index, and self-consumption of chicken meat came in second position with 0.34 as the index. According farmers, three phenotypes of chickens (